MAX BLECHER’S CENTRAL EUROPEAN AFFINITIES - Gabriela GLĂVAN (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
Max Blecher’s Central European Affinities. Max Blecher’s connections with the Central European literary imaginary, which scholars have established through readings that place Blecher in the proximity of authors such as Bruno Schulz or Franz Kafka, could be revisited not only comparatively, but also by tackling some key issues in his work and biography that may confirm the writer’s belonging to this vast intellectual territory. Provincial spaces, marginality, uncertainties regarding identity, existential confusion, immaturity, the pervasiveness of objects and of the artificial, they all reveal a perspective upon literature that may function, in the absence of a geographical belonging, as a bridge and connection between worlds that mirror each other’s essence and difference.